An approach to visual anthropology from Spanish academic journals (1940-2010) - Velasco, María Jesús (Revista General de Información y Documentación, 2015)
This research is based on the premise that an understanding of cultural phenomena has to deal with the conjunction of these two modes of knowledge: scientific knowledge and knowledge based on the aesthetic and symbolic dimension of the images. The most relevant Spanish academic journals in the field of anthropology from 1940 to 2010 are analyzed, focusing on the use of images produced in the field of anthropology and/or from other areas of our visual culture.Our conclusion is that the journals of the field of anthropology provide a good material to verify the prevalence of text on images in the academy. This research, therefore, highlights the need of opening new spaces, at a conceptual and formal level, in which images can be a regular part of anthropological knowledge it from a holistic perspective.